100 science experiments - Andrews, Georgina; Allman, Howard; Baggott, Stella; Knighton, Kate. ([London] : Usborne ; Tulsa, Okla. : EDC Pub., 2012)
A collection of one hundred science experiments designed to provide hands-on experience with scientific investigation, as well as the science behind the experiments.
Includes index.
Spine title: Usborne Internet-linked 100 science experiments.
5.7
3-6.
3-6
Keywords: Science -- Experiments -- Juvenile literature; Science -- Experiments; Science -- Experiments